2012
DOI: 10.4103/2249-4847.96739
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Rational and Cost-Effective Use of iNO Therapy in Term and Preterm Infants

Abstract: Inhaled nitric oxide (iNO) is an effective but costly therapy for infants with hypoxemic respiratory failure. The approved and solidly evidence-based indication is for treatment of late preterm and term infants with persistent pulmonary hypertension of the newborn (PPHN); however, off-label use of iNO has become widespread. Although iNO treatment of infants with congenital diaphragmatic hernia constitutes one of the approved indications, available evidence from randomized trials suggests marginal if any effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…However, a retrospective post hoc analysis of this study suggested that a subset of premature infants with preterm prolonged rupture of membranes (pPROM), oligohydramnios, and pulmonary hypoplasia may have benefitted from iNO therapy. 11 Similar conclusions were derived from other case reports/series linking pPROM to improved survival with iNO in preterm infants [12][13][14] possibly because of a transient defect in NO generation with pPROM. 15 The existence and the hemodynamic and histological features of early pulmonary hypertension (PH) and HRF in preterm infants are subjects of controversy.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…However, a retrospective post hoc analysis of this study suggested that a subset of premature infants with preterm prolonged rupture of membranes (pPROM), oligohydramnios, and pulmonary hypoplasia may have benefitted from iNO therapy. 11 Similar conclusions were derived from other case reports/series linking pPROM to improved survival with iNO in preterm infants [12][13][14] possibly because of a transient defect in NO generation with pPROM. 15 The existence and the hemodynamic and histological features of early pulmonary hypertension (PH) and HRF in preterm infants are subjects of controversy.…”
supporting
confidence: 63%
“…Similar to these findings, other investigators have observed the beneficial effect of iNO in preterm infants with HRF and pPROM. [11][12][13][14]…”
Section: Prenatal Corticosteroidsmentioning
confidence: 99%
“…However, the mortality rate for HRF in term and late preterm patients is approximately 11% and has remained relatively constant since the FDA approval of iNO in 1999 [9]. Therefore, interest is growing in developing rational approaches to treating term and near-term infants that include defining iNO responders so that other therapies, such as ECMO, can be initiated in a timely manner [4, 1012]. Indeed, a lack of oxygenation response within 1 h has been suggested as a criterion for discontinuing iNO [4].…”
Section: Introductionmentioning
confidence: 99%
“…iNO has been considered an advantage over traditional treatment measures for the above diseases due to its ability to improve oxygenation by selectively vasodilating the pulmonary vasculature [Steinhorn, 2010]. Currently, iNO is used successfully in the late preterm and term population of patients with persistent pulmonary hypertension (PPHN) [Keszler, 2012]. However, its use in other paediatric respiratory diseases has been associated with differential outcomes.…”
Section: Introductionmentioning
confidence: 99%